Hospitaller Castles and Fortifications in the Kingdom of Jerusalem, 1136-1291 - Denys Pringle (Medievalista)
This paper presents a historical and archaeological overview of the castles and other fortifications built and occupied by the Order of the Hospital of St John in the Kingdom of Jerusalem between 1136, when the order acquired the castle of Bayt Jibrīn, and the final Mamluk siege of Acre in 1291, during which it defended a section of the city walls. Topics discussed include the order’s contribution to the defence of towns and cities in which they were not the sole or even the major property owner, as well as their own construction and possession of a range of other fortifications from major castles to lesser structures, including towers and maisons fortes. In each case, equal attention is paid to the buildings themselves and to the administrative system of bailiffs and castellans through which they were managed and operated. As the military situation became ever more precarious during the 13th century, the order also took over and briefly held three major castles, whose owners were unable to defend them: Ascalon between 1241 and 1247, Mount Tabor between 1255 and 1263, and Arsūf between 1261 and 1265.